The Effectiveness of Implementing Discussion Method to Improve Pre-Service Elementary Teachers’ Activeness in Social Science Learning - Guslinda, Guslinda; Munjiatun, Munjiatun (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
The implementation of this research was motivated by a lack of activity and student participation in lectures on elementary school social studies. Students tend to be silent without showing activity during lectures. This is certainly far from what is expected that in the lecture students should ideally participate actively in asking, answering, recording the essence of the lecture, presenting, and concluding the lecture material. The subject of the study was a student of the 2017 B class, which numbered 39 people. The formulation of the problem in this study is whether the application of effective discussion methods to increase the activeness of FKIP UNRI PGSD students in elementary school social studies. The purpose of this study was to determine the effectiveness of the application of the discussion method in elementary school social studies lectures at the FKIP UNRI PGSD students. This type of research is descriptive with qualitative methods. Data collection techniques are observation and interview techniques. Based on the research data analysis shows that the activeness indicators ask questions, from the four active student meetings an average of 22 people 56. people (61.53%) and Activity Indicators present 26 people (66.66%).41%, indicators respond to questions or opinions, active students 22 people 56.41%, Activity Indicators discuss and work together with active students 26 people (66.66%), Activity Indicators write material and summarize active student material 24. Based on the data that has been obtained, it can be concluded that the application of the discussion method in elementary school social studies